MORPHOLOGICAL EVOLUTION OF THE BOTTOM OF THE POTOU LAGOON OVER THE LAST TEN YEARS (COASTAL ZONE OF COTE D'IVOIRE) - Eric, DIANGONE; Colette, AKOBE Apie; Mireille, Amani Etché; Sylvain, MONDE; Aoua, COULIBALY (International Journal of Research -GRANTHAALAYAH, 2020)
This study with a morphology and hydrosedimentology character was done to carry out a with an understanding the evolution of the channels and sedimentation in Potou lagoon in Ivory Coast starting from the realization of the bathymetric map. The bathymetry of this lagoon avered that the depths are lower than 2.11 m out of 22 km2, and presente three types of channels. In fact the channels in "U" represent a balance between the agents of accumulation and erosion. Channels resulting from processes of erosion which are in "V" and channels intermediate indicating an evolution of the type "V" in "U". In particular during these fourteen last years the Potou lagoon has sudden great phenomenon of deposit is a volume of +66791000.18 m³of sediments deposed on a surface which is thus estimated at 65.2 % of chenal surface. These deposits are certainly causes of full high funds in this lagoon. The mean velocity of sedimentation on Potou lagoon is thus estimated at 26.5 cm/year. As for the erosion, it could be estimated at-8487601 m³ a volume of on a surface wich is thus estimated at 34 % of chenal surface. The sedimentary budget would be thus estimated at+58303398.68449 m³ on a surface of 12.45 m2. A surface which is thus estimated at 0.8 %hasn’t sudden phenomenon of deposit or erosion. The bathymetric chart and the sedimentary budget of Potou lagoon are tools necessary for use of the stretch of water by the users. Thus, the zones at the risks determined on the bathymetric chart, such as the high bottom and the points of swirl generated by the depressions, will be easily avoided.